Design and establishment of perforating-vein fistula in forearm - LU Shi; WANG wei; YU Xiu-zhi; HAN Guo-feng; HU Wei-feng (Linchuang shenzangbing zazhi)
Objective The purpose of this paper is to explore the establishment methods and clinical application of perforating-vein fistula surgery. Methods A total of 88 cases of patients undergoing forearm perforating-vein fistula surgery from May 2017 to May 2018 in our hospital were selected, including 38 males and 50 females, with an average age of(59.0±11.9) and average dialysis age of(37.6±54.4) months. There were 74 cases of anastomosis of the vascular side after ligation of perforating veins and 14 cases of vascular end-to-side anastomosis after cutting perforating veins. Results There were 87 patients with successful operations at a time and one with failing operation. At 1～3 months after operation, among 72 patients followed up, in 69 ones the established fistula was successfully used for dialysis puncture [dialysis blood flow(209.7±13.1 mL/min)] and in 2 ones the puncture had difficulty as the fistula was immature. One patient died unexpectedly one months after surgery. There were 39 cases of patients with puncture at the distal anastomosis, accounting for 56.52%. Conclusions For the patients with poor vascular condition in the wrist and forearm, it is not possible to make or reconstruct the ideal internal fistula, and establishment of the upper forearm perforating-vein fistula may obtain satisfying clinical effectiveness.